Pola Interaksi Sosial Guru Akidah Akhlak Dalam Merespon Maraknya Perilaku Phubbing Dikalangan Pelajar (Studi Kasus Di Man Kota Batu) - Fandi, Heryan; Surya Sorayya Putri, Lintang (CV Kalimasada Group, 2023)
Phubbing is a phenomenon in which a person ignores the other person by focusing on their smartphone. This phenomenon is very prone to occur among students who are already familiar with the development of science and technology. The purpose of this study is to: (1) Know the phenomenon of phubbing that occurs in the learning process at MAN Batu City. (2) Knowing the supporting and inhibiting factors of the teacher's Akidah Akhlak interaction pattern with students at MAN Batu City during the learning process. (3) Knowing the efforts of MAN Batu City Akidah Akhlak teachers in responding to phubbing phenomena among students. This study uses a descriptive qualitative method. The results of this study are: (1) The phubbing phenomenon is found with an attitude of dependence and hurt. (2) Efforts made by the teacher to respond to phubbing behavior include making learning contracts, approaching the interaction patterns used, and collaborating with homeroom teachers and counseling teachers. (3) In responding to phubbing behavior, MAN Batu City Akidah Akhlak teachers apply an educational interaction pattern by prioritizing good communication. The supporting factors of the interaction pattern used are enthusiasm, school curriculum, and adequate infrastructure. While the inhibiting factors are the demand to always follow the development of science and technology, and the unfavorable family environment of students.